An efficient, broad-band red-emitting Li2MgTi3O8:Mn4+ phosphor for blue-converted white LEDs - Zhang, Shaoan; Hu, Yihua; Duan, He; Fu, Yinrong; He, Miao (Journal of alloys and compounds, 2017)
We describe the preparation of a novel red-emitting Li2MgTi3O8:Mn4+ nanocrystalline phosphor by a soft chemical method. Li2MgTi3O8:Mn4+ phosphor gained our attention and interest due to its low-cost and unique luminescent properties. The deep red emission from Li2MgTi3O8:Mn4+ shows an abnormal broad band at 680 nm, with a quantum efficiency (QE) of 34%, and good thermal resistance of ΔE = 0.214 eV Li2MgTi3O8:Mn4+ phosphor exhibits the most intense excitation absorption in the blue region which matches the emission wavelength of the blue LEDs, indicating its potential to enhance the color rendering performance of white LEDs. The deep red emission originates from the 2Eg → 4A2g transition of Mn4+. The spectral features are well explained by the Tanabe-Sugano diagram, with crystal-field and Racah parameters of Dq = 2.06 × 103 cm−1, B = 0.76 × 103 cm−1 and C = 3.00 × 103 cm−1. A device was fabricated in which this red phosphor Li2MgTi3O8:Mn4+ was used to coat the blue LEDs. The fabricated device demonstrated that the prepared material can act as a novel potential red phosphor for warm white LEDs. [Display omitted] •A novel red phosphor Li2MgTi3O8:Mn4+ was prepared by the soft chemical method.•Li2MgTi3O8:Mn4+ gives a deep red emission with a good QE and thermal resistance.•Li2MgTi3O8:Mn4+ can act as a novel potential red phosphor for warm white LEDs.